A companion to European Romanticism - Ferber, Michael, 1930- (Malden, MA ; Oxford : Blackwell Pub., 2005)
Describes the way in which the Romantic Movement swept across Europe in the early nineteenth century, transforming literature, music, painting, religion, philosophy, politics and personal relationships. Focussing on the whole of European Romanticism, the volume also includes cross-disciplinary contributions in over 30 essays.
A Companion to European Romanticism; Contents; Notes on Contributors; Introduction; 1 On Pre-Romanticism or Sensibility: Defining Ambivalences; 2 Shakespeare and European Romanticism; 3 Scottish Romanticism and Scotland in Romanticism; 4 Byron's Influence on European Romanticism; 5 The Infinite Imagination: Early Romanticism in Germany; 6 From Autonomous Subjects to Self-regulating Structures: Rationality and Development in German Idealism; 7 German Romantic Fiction; 8 The Romantic Fairy Tale; 9 German Romantic Drama; 10 Early French Romanticism.
Print version record.
Keywords: Romanticism; Romantisme; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Romanticism; Romantisme; Electronic books